KEPATUHAN IBU MENYUSUI DALAM PEMBERIAN ASI EKSKLUSIF PADA BALITA DI DESA SAMBIROTO LECAMATAN KAPAS KABUPATEN BOJONEGORO - Woro Tri Utami, Woro Tri Utami; Sulit Dwi R, Sulit Dwi R (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2014)
Exclusive Breastfeeding is giving breastfeeding ( breast milk ) as early as possible after birth, given no timetable and no other food , although water until the baby is 6 months of age after the age of 6 months babies should be given extra food and breast milk should still be given to infants aged 2 years . While adherence to breastfeeding mothers breastfeeding mothers in breastfeeding their babies exclusively on already severe . The purpose of this study was conducted to determine the extent of compliance in Breastfeeding mothers exclusively breastfed their babies . The method used in this research is descriptive method by simple random sampling , a total sample of 30 respondents . Data collection using questionnaires then the data processing process by giving code then tabulated scores . This research was conducted in the village of kapas Sambiroto District of Bojonegoro in 2013.It can be concluded that the level of compliance in Breastfeeding mothers exclusively breastfed their babies in category submissive . It is effected because the level of education and age . The respondents most elementary level of education and all respondents aged 0 years , but despite that knowledge of the respondents about the level of knowledge about exclusive breastfeeding mothers quite well . Keywords : compliance Breastfeeding mothers , exclusive breastfeeding , toddler